DEVELOPMENT OF INTEGRATED SCIENCE LEARNING DEVICES USING PROBLEM BASED LEARNING (PBL) LEARNING MODEL THROUGH LESSON STUDY - Sarlota Singerin; Estevanus K Huliselan; Altje Latununuwe (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2020)
The study was conducted at SMP Negeri 2 Salahutu. The purpose of this study is to develop a science learning tool using the Problem Based Learning learning model, through lesson study. The research design uses the 4 D Research and Development research method (Define Phase, design, develop, Disseminate). The application of products in the form of PBL-based integrated science-oriented learning modules through LS results in the following findings: 1). The Global warming theme module is based on curriculum analysis, student and teacher needs and field observations; 2). The Global warming theme module is able to get students actively involved in the learning process. 3). PBL-based Global warming theme modules through Lesson Study train students' creativity; 4). The teacher's knowledge about the systematic writing of the modules is still lacking so that the writer at the time of dissemination gave a presentation on the systematic module. The results of this study found that 1). Development of Integrated Science Learning Using Models of Problem Based Learning through Lesson Study can improve the student learning outcomes; 2). Development of Integrated Science Learning based on Problem Base Learning through Lesson study using the Global warming theme module is based on curriculum analysis, student and teacher needs and field observations. This module is able to make students actively involved directly in the learning process and train students' creativity